Cold water immersion recovery following intermittent-sprint exercise in the heat - Pointon, M.; Duffield, R.; Cannon, J.; Marino, F. E. (European Journal of Applied Physiology, 2012)
This study examined the effects of cold water immersion (CWI) on recovery of neuromuscular function following simulated team-sport exercise in the heat. Ten male team-sport athletes performed two sessions of a 2 × 30-min intermittent-sprint exercise (ISE) in 32°C and 52% humidity, followed by a 20-min CWI intervention or passive recovery (CONT) in a randomized, crossover design. The ISE involved a 15-m sprint every minute separated by bouts of hard running, jogging and walking. Voluntary and evoked neuromuscular function, ratings of perceived muscle soreness (MS) and blood markers for muscle damage were measured pre- and post-exercise, immediately post-recovery, 2-h and 24-h post-recovery. Measures of core temperature (Tcore), heart rate (HR), capillary blood and perceptions of exertion, thermal strain and thirst were also recorded at the aforementioned time points. Post-exercise maximal voluntary contraction (MVC) and activation (VA) were reduced in both conditions and remained below pre-exercise values for the 24-h recovery (P < 0.05). Increased blood markers of muscle damage were observed post-exercise in both conditions and remained elevated for the 24-h recovery period (P < 0.05). Comparative to CONT, the post-recovery rate of reduction in Tcore, HR and MS was enhanced with CWI whilst increasing MVC and VA (P < 0.05). In contrast, 24-h post-recovery MVC and activation were significantly higher in CONT compared to CWI (P = 0.05). Following exercise in the heat, CWI accelerated the reduction in thermal and cardiovascular load, and improved MVC alongside increased central activation immediately and 2-h post-recovery. However, despite improved acute recovery CWI resulted in an attenuated MVC 24-h post-recovery.